Team 19 in Vietnam : an Australian soldier at war - Millie, David (Foreign military studies., 2013)
Historical accounts and memoirs of the Vietnam War often ignore the participation of nations other than Vietnam and the United States. As a result, few Americans realize that several members of the Southeast Asian Treaty Organization (SEATO), including Australia, allied with South Vietnam during the conflict. By the late 1960s, more than eight thousand Australians were deployed in the region or providing support to the forces there. In this book, the author offers an insightful account of his twelve-month tour with the renowned Australian Army Training Team Vietnam in Quang Tri Province - a crucial tactical site along the demilitarized zone that was North Vietnam's gateway to the south. Drawing from published and unpublished military documents, his personal diary, and the letters he wrote while deployed, the author introduces readers to the daily routines, actions, and disappointments of a field staff officer. He discusses his interactions with province senior advisor Colonel Harley F. Mooney and Major John Shalikashvili, who would later become chairman of the U.S. Joint Chiefs of Staff. This firsthand narrative demonstrates the importance of the region and the substantial number of forces engaged there. This memoir also reveals that responsibility for the catastrophe inflicted on Vietnamese civilians is shared by an international community that failed to act effectively in the face of a crisis.